2021
DOI: 10.1002/admi.202100725
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Durable Superhydrophobic Polythiophene/SiO2 Coated Cotton Fabric for Versatile Oil–Water Separation

Abstract: With the development of industrialization, environmental pollution problems (e.g., oily water discharge and oil spill accidents) are becoming increasingly severe. The efficient and economic treatments for oily sewage are urgently needed and remain a huge challenge. Here, a robust and durable superhydrophobic material with the contact angle above 160° is prepared by coating SiO2 particles/polythiophene on cotton fabrics through a sol–gel process and an oxidation coupling polymerization. The polythiophene/SiO2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…3g). 56 First, the cotton fabric was coated with micro-nano SiO 2 via a gel–sol method, and then polythiophene (PTh) was conjugated and modified by oxidative coupling polymerization. Experiments have shown that the modified fabric has good superhydrophobicity with a contact angle of up to 160° in water.…”
Section: Nature-inspired Oil–water Separation Materialsmentioning
confidence: 99%
“…3g). 56 First, the cotton fabric was coated with micro-nano SiO 2 via a gel–sol method, and then polythiophene (PTh) was conjugated and modified by oxidative coupling polymerization. Experiments have shown that the modified fabric has good superhydrophobicity with a contact angle of up to 160° in water.…”
Section: Nature-inspired Oil–water Separation Materialsmentioning
confidence: 99%
“…Aphra et al 22 reported simple synthesis of Janus mixed sustainable cellulose nanofibers (CNFs) sponge with asymmetric wettability, superb mechanical properties, and excellent separation purity for oil–water emulsions. Bai et al 23 coated SiO 2 particles/polythiophene on the cotton fabric through sol–gel process and oxidative coupling polymerization and prepared a strong and durable superhydrophobic material with contact angle greater than 160. This material was employed for gravity separation of oil–water mixture with high separation purity and reusability.…”
Section: Introductionmentioning
confidence: 99%